2018
DOI: 10.1007/s10640-018-0239-7
|View full text |Cite
|
Sign up to set email alerts
|

Natural Disasters and Macroeconomic Performance

Abstract: Recent empirical research has shown that output and GDP per capita in the aftermath of natural disasters are not necessarily lower than before the event. In many cases, both are not significantly affected and, surprisingly, sometimes they are found to respond positively to natural disasters. Here, we propose a novel economic theory that explains these observations. Specifically, we show that GDP is driven above its pre-shock level when natural disasters destroy predominantly durable consumption goods (cars, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Little evidence is found for the accumulation of human capital by meteorological disasters, but geological disasters are shown to have negative impact on human capital accumulation. [32] point out that although natural disasters lead to considerable welfare losses, disasters are shown to have no significant impact on per capita GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Little evidence is found for the accumulation of human capital by meteorological disasters, but geological disasters are shown to have negative impact on human capital accumulation. [32] point out that although natural disasters lead to considerable welfare losses, disasters are shown to have no significant impact on per capita GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We compute the distribution of losses and their dynamics over time across sectors at a higher level of detail than previous studies. Models featuring endogenous dynamics such as CGE models, even though they depict up to 35 industry sectors as in [30], typically are comparative static CGE models 10 [30-32], while fully dynamic CGE models usually depict only one output good as in [29]. Furthermore, they often are confined to regions smaller than a national economy [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Indirect economic effects from natural disasters are difficult to model with traditional approaches such as inputoutput (IO) models [22][23][24][25][26][27][28], computable general equilibrium (CGE) models [29][30][31][32][33][34], and econometric analyses [7][8][9][10][11][12][13][14][15][16][17][18][19]35] because of the over-simplifying nature of these approaches [36]. IO models have a tendency to overestimate indirect economic losses and gains [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gross domestic product (GDP) is often used to quantify the indirect economic impact of disasters (Botzen et al 2019). Based on previous studies, disasters can have varying effects-both positive and negative-on GDP (Chhibber and Laajaj 2008;Panwar and Sen 2019;Strulik and Trimborn 2019). If a disaster causes severe damage, GDP tends to decrease; however, if the damage from a disaster is minor, GDP tends to increase (Chhibber and Laajaj 2008).…”
Section: Introductionmentioning
confidence: 99%
“…If a disaster causes severe damage, GDP tends to decrease; however, if the damage from a disaster is minor, GDP tends to increase (Chhibber and Laajaj 2008). Strulik and Trimborn (2019) found that the effects of disasters on GDP depend on a community's welfare spending. If a disaster occurs in a country with high welfare spending, GDP may grow as a result of citizens' increasing consumption to replace assets that were destroyed.…”
Section: Introductionmentioning
confidence: 99%